Bandpass Filter Based on Spoof Surface Plasmon Polaritons With a Switchable High-Selectivity Notch Band - Tan, Longfei; Wang, Qiangji; Guo, Ying-Jiang; Cui, Jianlei; Xu, Kai-Da (Frontiers in Physics, 2021)
A substrate integrated waveguide (SIW) based spoof surface plasmon polariton (SSPP) is proposed for the design of bandpass filter (BPF). The left and right edge cutoff frequencies of the passband can be easily adjusted by changing the parameters of SIW and ring slot embedded into the SIW. Then, four half-wavelength circular slots are added on two sides of the SSPP located at the center of the circuit to introduce a high-selectivity notch band. In order to make the notch band switchable, four full-wavelength circular slots and four PIN diodes are applied instead of the four half-wavelength circular slots. As the PIN diodes are under the ON state, the notch band will be generated within the passband of BPF. On the contrary, as the PIN diodes are under the OFF state, the notch band will disappear. To validate the design idea, two BPF examples are fabricated and measured, whose simulation and measurement results are both in reasonably good agreement.